EXTEMPORANEOUS MANUFACTURING OF INTRAVENOUS ADMIXTURES IN HOSPITAL PHARMACIES OF RUSSIAN FEDERATION - G. N. Kovalskaya; E. N. Mikhalevich (Фармация и фармакология (Пятигорск), 2017)
The provision of patient-centered pharmaceutical care is carried out through pharmaceutical organizations and is accompanied by such necessary functions as counseling, provision of information on drugs, monitoring of drug therapy. It also includes ensuring quality, effective and safe drugs. In this case, the role of pharmacies is reduced to providing the population with ready-made products of industrial production. The problem of improving the technology of infusion solutions assigned in stationary conditions, including combined drugs of individual manufacture is especially acute.The aim of this work was to study and analyze the options for the extemporaneous manufacture of combined drugs for infusion introduction in hospital pharmacies.Materials and methods. The methodological basis of the study was a systemic approach, which makes it possible to identify the key elements of two different options for the extemporaneous manufacture of combined drugs for infusion administration. The research uses methods of logical and functional analyses.Results and discussion. The analysis of scientific sources on the issues of manufacturing of combined infusion solutions for the needs of stationary patients showed that manufacturing is carried out according to the traditional scheme for the Russian Federation, i.e. in the conditions of the procedural room of the department. In pharmacies of medical organizations, two variants of small-scale extemporal manufacture of combined infusion solutions are permissible using pharmaceutical substances and using sterile drugs of industrial production. The presence of a number of critical points of the first variant shows the irrationality and limitations of the use of such a scheme for the manufacture of combined infusion solutions in the pharmacy of a medical organization. The second version of the extemporal manufacture of combined infusion solutions is characterized by the simplicity of the technological scheme, the absence of complex calculations, a number of preparatory operations, filtration and sterilization steps, a simplified version of quality control, and the lack of complex equipment. This allows the rapid and large-scale production of various combinations of drugs for infusion.Conclusion. Manufacturing intravenous admixtures from commercial medicines allows the rapid and large production of various combinations of drugs for infusion introduction, does not contradict the current legislation, which makes it possible to consider it as the main variant of manufacturing of combined infusion solutions in hospital pharmacies.